Laryngopharyngeal Reflux Disease: Microbial Signatures and Their Associations With Clinical and Digestive Enzyme Profiles - Jérôme R. Lechien; Patricia B. Rodrigues; Nathalie De Vos; Anne Trelcat; Vinciane Muls; Jennifer Aoun; Didier Dequanter; Alexandra Rodriguez; Stéphane Hans; Giovanni Briganti; Amandine Everard; Sven Saussez (Otolaryngology–Head and Neck Surgery, 2026)
Abstract Objective To characterize the salivary microbiome of patients with laryngopharyngeal reflux disease (LPRD) and investigate its associations with clinical presentation and salivary gastroduodenal enzymes. Study Design Prospective controlled study. Setting University Hospital. Methods Saliva samples from patients with LPRD at the 24‐hour hypopharyngeal‐esophageal multichannel intraluminal impedance‐pH testing and asymptomatic individuals were consecutively collected for analyzing digestive enzyme/biomarker (pepsin, elastase, bile salts, cholesterol, trypsin) and microbiome features (16S rRNA IlluminaMiSeq). Pretreatment to posttreatment symptoms and findings were evaluated with reflux symptom score and reflux sign assessment. Association between microbiome abundance, enzyme concentration, and baseline and post‐treatment clinical findings were assessed. Results Sixty‐seven LPRD patients (40 females [59.7%]) and 44 controls (26 females [59.1%]) completed the evaluations. LPRD patients demonstrated significantly higher concentrations of elastase, higher salivary pH, and lower levels of cholesterol compared to controls. The comparative analysis of salivary microbiota between LPRD patients and controls demonstrated significant taxonomic‐level alterations in alpha diversity (reduced Shannon index at family and genus levels in LPRD, P < .006) and beta diversity (distinct community composition by UniFrac metrics, PERMANOVA, P ≤ .005), with differential abundance of key taxa including a modulation of Streptococcus species, elevated Actinomyces and Abiotrophia , and depleted Oribacterium and Eubacterium nodatum group in LPRD patients compared to controls. Elastase, trypsin, and bile salts reported significant association with relative abundance of some bacteria. Conclusion This preliminary study supports that LPRD patients exhibit distinct microbial signatures compared to asymptomatic subjects, characterized by reduced diversity at specific taxonomic levels, subtle shifts in community membership, and differential abundance of some key genera